Overview of Tien Kok Sie Temple in Solo City, Indonesia - Ruth Kiana Nuratri (Mandarinable: Journal of Chinese Studies, 2022)
Tien Kok Sie Temple is the oldest Chinese temple di Solo, Indonesia. It has a history of more than 300 years. Until this moment, many people will go to the temple to pray or have sightseeing this temple. Solo Cultural Department has announced that Tien Kok Sie Temple has become one of the cultural heritage buildings in Solo. Tien Kok Sie Temple also represents the integration of Chinese Culture into Indonesian local people, also it is very harmonious.